Pengaruh Pengeluaran Pemerintah Dan Investasi Terhadap Pertumbuhan Ekonomi Di Kabupaten Gowa - Magefiratil Aswar; Arniati, Arniati; Dg. Maklassa (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to examine the influence of government expenditure and investment on economic growth in Gowa Regency. The research employs a quantitative approach using multiple linear regression analysis and utilizes secondary data collected from 2014 to 2023. The results indicate that investment has a positive and significant effect on economic growth, as it plays a crucial role in increasing output and productivity. Meanwhile, government expenditure shows a positive but not significant effect, which may be due to the inefficiency in the allocation of government spending in driving economic growth.